EVALUASI KLINIS DAN PATOLOGIS INFEKSI Microsporum canis PADA ANJING DENGAN TERAPI KETOKONAZOLE, GRISEOFULVIN, DAN KOMBINASI KEDUANYA - , PUTU AYU SISYAWATI PUTRININGSIH, Dr. drh. Soedarmanto Indarjulianto ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Dermatophytosis is an infectious skin disease and potentially zoonotic caused by dermatophytes. The disease is often found in dogs. The clinical diagnosis of dermatophytosis is difficult to determine because the clinical symptoms of dermatitis is varied, however. Moreover, the above clinical diagnosis problem results in uneffective antifungal treatment in patients. This study aimed to evaluate the clinical and pathological features of dogâs skin which is infected with Microsporum canis, as well as to evaluate the efficacy of antifungal therapy. Twelve female and male dogs with the aged of 12 weeks were divided into 4 groups of 3. Group I treated with 2% ketoconazole cream that given 2 times a day (on the right flank) and as a negative control that is not infected and not treated on the left flank. Group II treated orally with 20 mg/kg BW griseofulvin once a day. Group III treated with a combination of both, and group IV untreated (positive control group). All groups were infected with M. canis suspension containing 36x105 spores cells/mL. Each dog infected by dripping a suspension of 20 Î¼L on the skin at the right flank. Lesion progress was observed up to day 14. Treatment with antifungal started from day 14 post-infection, administered daily for 21 days. The progress of clinical and pathological lesion observed during infection and therapy period with Wood's lamp, clinical examination and skin biopsy for histopathological examination. To establish infectious agent of ermatophytosis, the infected skin was scrapped and then cultured in Sabaroud Dextrose Agar (SDA). Hematoxylin-eosin and immunohistochemistry staining with anti-CD68 and anti-CD45 antibodies conducted to observe the morphologycal skin tissues abnormality in the epidermis, the dermis and the cells which is expressed CD68 and CD45. Therefore, clinical and pathological lesions were analysed descriptively, whereas antifungal treatment efficacy was analysed statistically using one-way ANOVA and posthoc Tukeyâs test and descriptively toward the epidermal thickness and the number of macrophages and lymphocytes that express CD68 and CD45 protein respectively. The observation of clinical lesions on the skin infected by M. canis demonstrated erythema, scale, crusting, circular alopecia, and hyperpigmentation. Histopathological features showed skin abnormality such as, epidermal hyperplasia, parakeratosis, dermal inflammation, the crusts and pieces of hyphae, as well as an increased in the number of inflammatory cells that express CD68 and CD45 protein. The decrease in the severity of both clinical and histopathological lesions seen in all treatment group after single and combination therapy. Statistically, therapeutic effect of topical and systemic antifungal significantly reduced epidermal thickness (p< 0,05). Interestingly, combination therapy significantly reduced epidermal thickness compared with griseofulvin therapy, but not with ketokonazole therapy (p>0,05). To conclude, the combination therapy of topical ketoconazole and systemic griseofulvin have therapeutic effect better than single antifungal therapy against clinical and pathological features of M. canis infection in dogs.